1994
DOI: 10.1093/oxfordjournals.aje.a116992
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Mortality and Polynuclear Aromatic Hydrocarbons: A Case-Cohort Study of Aluminum Production Workers in Arvida, Quebec, Canada

Abstract: The authors report the results of a case-cohort study of 338 lung cancer deaths in 1950-1988 and a random sample (sub-cohort) of 1,138 from among 16,297 men who had worked at least one year between 1950 and 1979 in manual jobs at a large aluminum production plant. In the past, certain workers were exposed to substantial quantities of coal tar pitch volatiles, a mixture known to include polynuclear (polycyclic) aromatic hydrocarbons, and thus suspected to be capable of causing lung cancer. After they controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
7

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(85 citation statements)
references
References 0 publications
2
76
7
Order By: Relevance
“…Before that, the exposure levels have probably been considerably higher. In Canadian aluminum smelters, where epidemiologic studies have revealed increased risks for both lung and bladder cancer for the workers, the TWA levels for B[a]P in air have been estimated to have been 10-20 pg/m3 during the relevant time period (2,3). According to a risk assessment model derived from these data, a mean B [alp exposure of 1 pg/ m3 during a 40-year period would result in a slightly less than doubled relative risk for bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before that, the exposure levels have probably been considerably higher. In Canadian aluminum smelters, where epidemiologic studies have revealed increased risks for both lung and bladder cancer for the workers, the TWA levels for B[a]P in air have been estimated to have been 10-20 pg/m3 during the relevant time period (2,3). According to a risk assessment model derived from these data, a mean B [alp exposure of 1 pg/ m3 during a 40-year period would result in a slightly less than doubled relative risk for bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This process has previously caused high airborne exposure levels of coal tar pitch volatiles, containing polycyclic aromatic hydrocarbons (PAH) (1). Potroom workers have increased risks for both bladder and lung cancer (2)(3)(4), probably due to the PAH exposure. Due to technical improvements in the plants, the airborne exposure levels have, however, been reduced during recent years.…”
mentioning
confidence: 99%
“…The exposure to PAHs in an aluminum production plant (Armstrong et al 1994) gave a quantitative risk estimate of 1 × 10 -5 per ng B[a]P/m 3 as workplace exposure for 40 years. If converted to lifetime continuous exposure, the corresponding lifetime unit risk for respiratory cancer would be approximately 9 × 10 -5 per ng/m 3 (70/40 years × 365/220 days × 24/8 hr).…”
Section: Epidemiologic Datamentioning
confidence: 99%
“…Based on the similarity of the PAH profiles in urban air and in an aluminum smelter workplace (seven measured PAH compounds; see Special Report • Boström et al below, "United Kingdom"), the panel concluded that occupational studies on workers at aluminum smelters form a suitable basis for recommending an environmental standard. The study chosen was the Canadian study on aluminum workers by Armstrong et al (1994). In this study, a 50% increase in the risk of lung cancer was demonstrated, with a cumulative exposure to B[a]P as indicator substance at levels of 10-100 µg/m 3 × year (equivalent to an exposure to 0.25-2.5 µg/m 3 B[a]P for 40 years).…”
Section: Epidemiologic Datamentioning
confidence: 99%
“…1,2 Similar findings have been reported among workers in aluminum smelters. [3][4][5][6][7] Two important anthropogenic sources of PAHs are the Söderberg primary aluminum vertical stud smelters (VSSs) and horizontal stud smelters (HSSs). The carbon anodes used in the process contain coal tar pitch, which acts as a binder.…”
Section: Introductionmentioning
confidence: 99%